Research on label propagation algorithm based on modularity maximization in the social network - Jing CHEN; Yun WAN (Tongxin xuebao)
A kind of community detection method based on the combination of modularity and community structure attributes was proposed.Firstly,updating the whole network after communities merging every time could result in the high time complexity,therefore,introducing propagation distance parameter and “merger going after label propagation” was utilized to reduce time complexity.Secondly,CDMM-LPA algorithm was proposed by combing label propagation with community structure.Finally,empirical analysis on data networks verified the validity of the approaches.The experimental results show that the CDMM-LPA algorithm has a high modularity value and a more stable community structure while reducing the time complexity.